Life-threatening arrhythmias leading to syncope in patients with vasospastic angina - Mitsuhiro Nishizaki (Journal of Arrhythmia, 2017)
The coronary artery diseases (CAD) that can lead to the occurrence of a syncopal attack include acute coronary syndrome, vasospastic angina, effort angina, and prior myocardial infarction. The possible mechanisms considered to lead to syncope in patients with CAD are pump failure, tachyarrhythmia, bradycardia, and vagal stimulation. Coronary artery spasm, in particular, is occasionally observed in patients with unexplained syncope in Japan. Life-threatening arrhythmias are among the most serious complications of an ischemic attack caused by coronary spasm, and are associated with an increased risk of syncope and/or sudden cardiac death (SCD). Therefore, during the initial evaluation of unexplained syncope, the diagnosis of vasospastic angina (VSA) needs to be made promptly, to avert the risk of SCD as a consequence of syncope triggered by the lethal arrhythmia. The inducibility of polymorphic ventricular tachycardia or ventricular fibrillation, increased QT dispersion, T-wave alternans, and early repolarization during the asymptomatic period are considered risk markers for ventricular arrhythmias during coronary spasm. In view of the conclusions from several studies, implantable cardioverter/defibrillator therapy should be considered in patients who are at high risk for recurrence of syncope due to a fatal ventricular arrhythmia triggered by coronary spasm, despite appropriate medical therapy. Keywords: Syncope, Coronary artery spasm, Vasospastic angina, Ventricular arrhythmia, Implantable cardioverter defibrillator